2004
DOI: 10.1080/03079450310001652059
|View full text |Cite
|
Sign up to set email alerts
|

In vivostudies ofGallibacterium anatisinfection in chickens

Abstract: The aim of the present study was to investigate the pathology in normal or immunosuppressed chickens followed intravenous or intraperitoneal inoculation with a well-characterized strain of Gallibacterium anatis. Two groups of 30 15-week-old commercial brown laying chickens were used, having been screened and found negative for Gallibacterium organisms. One group was treated with 5-fluorouracil to promote heterophil depletion, while the other was saline treated. Ten days later 15 chickens from each group were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 25 publications
5
77
0
1
Order By: Relevance
“…However, the number of heterophil granulocytes was drastically reduced in both treated groups 7 and 8 days after 5-FU treatment, 2 and 3 days after virus inoculation, when viraemia was expected. The results of the blood cell counts were too few to be statistically evaluated, but the effect of 5-FU on blood cells seemed already discussed in detail by Kogut et al (1993) and Bojesen et al (2004). The histological studies of bursa tissues confirmed the results of lymphocyte counts, revealing cellular depletion 5 days after 5-FU treatment.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, the number of heterophil granulocytes was drastically reduced in both treated groups 7 and 8 days after 5-FU treatment, 2 and 3 days after virus inoculation, when viraemia was expected. The results of the blood cell counts were too few to be statistically evaluated, but the effect of 5-FU on blood cells seemed already discussed in detail by Kogut et al (1993) and Bojesen et al (2004). The histological studies of bursa tissues confirmed the results of lymphocyte counts, revealing cellular depletion 5 days after 5-FU treatment.…”
Section: Discussionsupporting
confidence: 57%
“…A model for heterophil depletion of chickens by treatment with the cytostatic drug 5-flurouracil (5-FU) has been described (Kogut et al ., 1993) and used for investigation of the influence of heterophil granulocytes on bacterial (Bojesen et al ., 2004) andviral (Raj et al ., 1997) infections in chickens. In a previous, unpublished experiment, chickens treated with the recommended dose of 5-fluorouracil (5-FU) and subsequently infected with IBDV showed mild clinical symptoms, but survived the infection.…”
mentioning
confidence: 99%
“…In the present investigation, ascending infections may have contributed to the finding of G. anatis and E. coli in the reproductive tract, in addition to the heart, liver and spleen. Bojesen et al (2004) used fluorescence in situ hybridization to demonstrate bacteria in the spleen and liver following intraperitoneal infection of chickens with Gallibacterium, indicating that ascending infections might be of relevance. The gross pathological lesions of reproductive disorders due to Gallibacterium infection cannot be distinguished from infections with E. coli, and for this reason all samples were also investigated for E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a mortality of 73% was noted in experimentally immunosuppressed 15-week-old brown layers after intravenous infection, emphasizing the importance of Gallibacterium spp. as a pathogen (Bojesen et al, 2004). In a field study performed in Denmark, Bojesen et al (2003b) demonstrated that the biosecurity level influenced the prevalence of Gallibacterium spp., with a lower level of biosecurity resulting in a more frequent detection of these pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium is known to be a member of the normal upper respiratory tract and lower reproductive tract of chickens but has also been implicated in peritonitis and salpingitis in commercial laying hens (3)(4)(5)16). To this end, G. anatis has been experimentally shown to induce natural infection in the chicken model (2). While studies aimed at the molecular pathogenesis of G. anatis are limited, some potential virulence factors/functions have been identified, including the production of secreted metalloproteases (9), hemagglutinating activity (9), and the production of a cytolytic RTX toxin known as GtxA (11).…”
mentioning
confidence: 99%